(untitled) (Analysis in Theory and Applications, 2011)
The Lipschitz classes Lip(α,M), 0 < α ≤1 are defined for Orlicz space generated by the Young function M, and the degree of approximation by matrix transforms of f Lip(α,M) is estimated by n^−α.